The Effect of Educational Technology Development and Economic Growth on Open Unemployment in Indonesia - Aga Dwi Sintha; Agustinus Suryantoro; Mulyanto Mulyanto (Budapest International Research and Critics University, 2021)
This study aims to examine and analyze the determinants of the unemployment rate in Indonesia. This study uses secondary data from the Indonesian Central Statistics Agency (BPS). This study uses the panel data method which is a combination of cross section data covering 34 provinces and time series for 5 years from 2015-2019. Based on the Chow test and Hausman test, the most appropriate model in this study is the Fixed Effect Model (FEM). Based on the simultaneous test, the development of technology, education, and economic growth simultaneously have a significant effect on the open unemployment rate of 87.38 percent and the remaining 12.62 percent is influenced by other variables not included in this research model. Based on the validity test, technological developments have a significant positive effect on the open unemployment rate, while education and economic growth have a significant negative effect on the open unemployment rate in Indonesia.